Pengaruh Penggunaan Zat Pengatur Tumbuh Alami terhadap Perkecambahan Biji Cabai Katokkon - Reisky Megawati Tammu; Jessica Elfani Bermuli (BIOEDUSCIENCE, 2022)
Background: Katokkon is a local red pepper that is widely cultivated in the North Toraja Regency and several surrounding areas within the scope of South Sulawesi Province, Indonesia. This pepper has a spicy taste and a unique fruit shape like paprika in small size and is rich in nutrients such as ascorbic acid, carotenoids, and capsaicin so that it benefits human health and serves as one of the commodities that improve the people's economy. Katokkon pepper is adapted to grow well in upland areas so that cultivation outside this habitat requires certain efforts to be optimal. Seed germination is an important step in plant cultivation. Coconut water and shallots extract were commonly used as sources of growth regulators substances to stimulate seed germination. Therefore, this study aims to determine the effect of natural growth regulators substances on the Katokkon pepper seed germination. Methods: This study was conducted by a factorial randomized block design with two factors and three replications. The Katokkon pepper seeds were soaked in the 25%, 50%, and 75% of coconut water and shallots solution for 24 hours. Results: The treatment of coconut water with a concentration of 75% (ZAK3) has a significant effect on the percentage and speed of seed germination of Katokkon pepper. Conclusions: The greater concentration of natural growth regulators used, the greater the percentage of seed germination obtained. However, the effect of coconut water treatment on seed germination of Katokkon pepper was more significant than the shallots extract.